TIME-DEPENDENT DISK ACCRETION IN BINARY SYSTEMS - Lipunova, G. V.; Shakura, N. I. (Одеські астрономічні публікації, 2017)
The analytic investigation of time dependent accretion in disk is carried out. We consider a disk in a binary system at outburst which has fixed tidally truncated outer radius. The standard model (Shakura-Sunyaev 1973) of the disk is considered. The fully analytic solutions in two different opacity regimes are characterized by power-law variations of accretion rate with time. The solutions supply asymptotic description of the disk evolution after the peak of outburst while the disk is fully ionized. The X-ray flux of multicolor (black-body) α-disk is obtained to vary quasi-exponentially. The application to X-ray novae is briefly discussed concerning observed faster-than-power decays of X-ray light curves. The case of time dependent advective disk is mentioned.